Formulation and Comparison of Cobalt and Molybdenum Glucomannan Metallocomplexes - Chandira, Rajappa Margret; Pethappachtty, Palanisamy; Kesavan, Harish; Samy, Dominic Antony (Asian Journal of Biological and Life Sciences)
Metallopharmaceutics is regarded as the subject in which drugs are complex with metals like platinum, zinc iron, etc. It is becoming the field of interest in medical sciences including oncology and diabetes. In this study, molybdenum and cobalt are used to prepare the metal complexes using glucomannan as the ligand. Pre-formulation studies performed for the drug proved to be of optimal results, which included angle of repose and swelling index. Stability studies were conducted for a time period of three months. The post-formulation studies including UV analysis and dissolution studies using egg membrane were performed. The drug had a distinct but weak peak at 267 nm. Formulation batch F5 had the best dissolution rate in terms of sustainability. Release kinetic studies showed that F5 (Glucomannan 500 mg + cobalt 1000 mg) had a linearity of 0.997 in the Higuchi diffusion plot. This infers that the plant-based extracts which possess low but significant therapeutic activity can be improved by using metals.
Keywords: Formulation; Glucomannan; Metal complex; Metallopharmaceutics; Molybdenum and cobalt